국내에서 비육한 수입 생우의 도체등급 특성에 관한 연구 - 박범영; 조수현; 김진형; 이왕식; 김용곤; 안종남; 이종문; 윤상기; Park, B.Y; Cho, S.H; Kim, J.H; Lee, W.S; et al. (Journal of animal science and technology, 2003)
This study was conducted to provide the information for the carcass grading properties of imported beef cattles fed in Korea. The cattles from 4 different breed such as Hereford, Angus, Murray Grey, Hereford${×}$Angus were imported and slaughtered at 700kg(24 month). The Yield and Quality grading characteristics for 10 cattles from each breed were evaluated. Carcass weight of Murray Grey was lower than the other breed(p<0.05). The thickness of backfat was the lowest for Hereford(13.7mm) and followed by Hereford${×}$Angus(17.30mm), Angus(18.20mm) and Murray Grey(18.90mm). Hereford had the highest Yield index(64.63%) and Murray Grey had the lowest Yield index(62.43)(p<0.05). The frequency percentages of marbling degree for Angus having the 1++ over degrees were 50% which was the highest among the breed. In the frequencies of final carcass grades, Hereford produced 30% of B grade and 70% of C grade in Yield grade and the 3 grade produced in Quality grade. All carcasses of Angus were graded as the grade C in Yield grade and 20% carcasses of Angus had the 2 grade and 80% carcasses had the 3 grade in Quality grade. Murray Grey produced 10% of grade B and 90% of grade C in Yield grade and produced 10% of the 2 grade and 90% of the 3 grade in Quality grade. The Hereford${×}$Angus produced 100% of grade C in Yield grade and 100% of the 3 grade in Quality grade. 국내에 생우로 수입된 호주산 육우 Hereford, Angus, Murray Grey, Hereford${×}$Angus 각각 10두의 도체등급 특성을 비교 분석하여 수입생우의 국내 비육에 대한 기초자료를 제시하고자 실시하였다. 육량등급요인 중 등지방 두께는 Hereford종이 13.7mm로 가장 얇았으며, Angus, Murray Grey, Hereford${×}$Angus은 각각 18.20, 18.90, 17.30mm로 나타났다(p<0.05). 배최장근 단면적에서는 품종간 유의적인 차이가 나타나지 않았으며(p>0.05), 육량지수는 Hereford종이 64.63으로 가장 높았고, Murray Grey종이 62.43으로 가장 낮았다(p<0.05). 육질등급요인 중 육색은 다른 품종들에 비하여 Hereford종이 낮았으며, 지방색은 Angus종이 가장 높았다(p<0.05). 성숙도는 다른 품종에 비하여 Angus종이 가장 낮았으며(p<0.05), 근내지방도, 조직감에서는 품종간에 차이가 없었다. 품종별 근내지방도 등급 출현율은 Angus종이 근내지방도 1++등급 이상이 50%를 차지하여 가장 높았으며, Hereford종이 전두수 1++등급 미만으로 가장 낮게 나타났다. 품종별 최종 도체등급 출현율에 있어서 육질등급에서는 Angus종이 육질 2등급 출현율이 20%로 가장 좋았으며, Hereford종과 교잡종(Hereford$×$Angus)은 100% 육질 3등급으로 가장 저조한 성적을 보였다. 육량등급 출현율에 있어서는 Hereford종이 육량 B등급 출현율 30 %로 가장 좋은 성적을 보였으나, Angus종과교잡종(Hereford${×}$Angus)은 100% 육량 C등급으로 가장 저조한 성적을 보였다. 전체적으로 볼 때 교잡종은 전 두수 육질 3등급, 육량 C등급을 보여 육질 및 육량 면에서 가장 저조하였다. 본 연구결과 수입생우(거세우)는 한우거세우에 비하여 육량, 육질 모든 면에서 저조한 결과를 보였다. 그러나 비육시험에서 한우와 동일하게 시험을 하지 못한 면에서는 아쉬운 점이 있었으며, 한우거세우와 정확한 비교를 위해서는 동일조건에서 한우와 수입생우의 비교시험이 필요하다고 사료된다.